2012
DOI: 10.1080/02673037.2012.651109
|View full text |Cite
|
Sign up to set email alerts
|

Moving after Separation: The Role of Location-specific Capital

Abstract: This paper addresses the role of location-specific capital-the ties that bind people to a place-in which ex-partners of two-sex couples move after separation or divorce. The study uses data from the first and second waves of the Netherlands Kinship Panel Study (N ¼ 361) to test hypotheses on the impact of individual homeownership, prior residential history, and the nearby presence of parents on whether a separated person moves. Who owned the home and whether someone's expartner moved in upon partnership format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 19 publications
3
61
1
3
Order By: Relevance
“…In these studies, as I have reported elsewhere, different research groups have shown how childbirth (Clark, Deurloo & Dieleman, 1994), divorce (Dieleman & Schouw, 1989;Dewilde, 2008;Mulder & Wagner, 2012), and marriage (Odland & Shumway, 1993;Mulder & Wagner, 1993) influence the likelihood of a move. Migration (a longer distance move) or mobility within the city are then adjustment processes which allow individuals and families to bring their locations in line with their perceived needs for specific locations and quantities of housing in response to the change created by the specific event.…”
Section: Previous Research and The Context Of Residential Movesmentioning
confidence: 90%
“…In these studies, as I have reported elsewhere, different research groups have shown how childbirth (Clark, Deurloo & Dieleman, 1994), divorce (Dieleman & Schouw, 1989;Dewilde, 2008;Mulder & Wagner, 2012), and marriage (Odland & Shumway, 1993;Mulder & Wagner, 1993) influence the likelihood of a move. Migration (a longer distance move) or mobility within the city are then adjustment processes which allow individuals and families to bring their locations in line with their perceived needs for specific locations and quantities of housing in response to the change created by the specific event.…”
Section: Previous Research and The Context Of Residential Movesmentioning
confidence: 90%
“…Ownership of the home also creates ties. In cases where only one expartner owned the home, it is almost exclusively that ex-partner who stays in the home and the other who moves out (Feijten and Mulder 2010;Mulder and Wagner 2012). The situation is more complicated when the partners jointly own the home.…”
Section: The Costs Of Moving Out: Hypotheses and Findingsmentioning
confidence: 98%
“…Having lived in the home before the start of the partnership arguably results in stronger ties to the home than having moved in with the partner. Evidence indeed suggests that having had the partner move into one's home decreases the likelihood of moving out (Mulder and Wagner 2012). Ownership of the home also creates ties.…”
Section: The Costs Of Moving Out: Hypotheses and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stream of studies has found that ex-partners who have custody of children (Gram-Hanssen and Bech-Danielsen 2008;Mulder and Wagner 2010), who are older (Mulder and Wagner 2010;, and those whose family members live nearby (Mulder and Malmberg 2011;Mulder and Wagner 2012) are less likely to move out of the joint home upon separation. Additionally, using data from the Netherlands, showed that the woman was more likely to move out if the home was owner-occupied.…”
Section: Previous Research On Separation and Housingmentioning
confidence: 99%